2021
DOI: 10.1111/jan.14976
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of missed infection control care: A tri‐partite international study

Abstract: Aim This study aimed to quantify types and frequencies of missed infection control care and to develop a theoretical model for estimating nurses’ consensus scores about this form of missed care. Design A non‐experimental research design using self‐audit data was selected to collect information about the types and frequencies of missed infection control care from nurses employed in hospitals located in three different countries. Data collection commenced mid‐year 2018. Methods A multivariate approach was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Thus, the item “turning patients every two hours” mainly to prevent pressure sores may have been misinterpreted or attributed less meaning. Moreover, the list of items included was not able to reflect the practices required to prevent the spread of infection as infection prevention/control programmes [ 49 ]. Thus, instruments may have missed the capacity to capture some specific elements of care required during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the item “turning patients every two hours” mainly to prevent pressure sores may have been misinterpreted or attributed less meaning. Moreover, the list of items included was not able to reflect the practices required to prevent the spread of infection as infection prevention/control programmes [ 49 ]. Thus, instruments may have missed the capacity to capture some specific elements of care required during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 15 years, there have been numerous international studies demonstrating evidence of inadequate care delivery, manifesting itself as poor residential aged care (Blackman et al, 2019), compromised patient safety (Kalisch et al, 2011), impaired infection control (Blackman et al, 2021) and inadequate mother and childcare (Blackman et al, 2020). Lack of care exists both in the community (Phelan et al, 2018) and in the acute care environments (Duffy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This review also provides important and detailed information on the nature of missed nursing care and shows that all manner of care is liable to being missed, including personal hygiene, skin care, oral care, discharge preparation, assistance with food and hydration, medications and infusions and hand hygiene. Blackman et al (2022) focused on issues around infection control and found that 13 variables exerted influence on missed infection control care, including methods used to prevent hospital‐acquired infections, surveillance and hand hygiene practices.…”
mentioning
confidence: 99%